Perbandingan Membaca Dan Menyimak Terhadap Kemampuan Working Memory Pada Gangguan Demensia Di Surakarta - Mafilahijra, Syahvania; Putra, Sinar Perdana; Sudarman, Sudarman (LPPM Hang Tuah Pekanbaru, 2025)
Dementia is a complex disorder with the main symptom being a decline in areas of cognitive function, one of which is working memory. Working memory plays a role in cognitive-linguistic. If language ability decreases, then language skills are also disturbed, so it needs to be improved with activities such as reading and listening. The aim of this study was to compare reading and listening skills to working memory in people with dementia. This study employs a quantitative method with a cross-sectional design. The sample obtained amounted to 12 people based on the Slovin formula and the sampling technique using cluster random sampling. Data collection lasted 10 days, around October-November. Dementia screening using the MMSE form, working memory using the Numerical Memory Check form, reading and listening using a questionnaire that has been tested for validity and reliability. The results of bivariate analysis using multiple linear regression with a coefficient obtained a value of p = 0.381 and p = 0.708, and multivariate analysis with ANOVA obtained a value of p = 0.653, indicating that no analysis of the comparison of reading and listening to working memory ability in dementia disorders was conducted. In conclusion, there is no comparison between reading and listening and working memory ability in dementia disorders in Surakarta.